Find the sum and choose the correct answer.
5n^3 + 4n^2 - 9 + (-2n^3 + 7n - 5)
-3n3 - 4n2 - 7n - 4
3n3 + 4n2 + 7n - 14
3n3 + 4n2 + 7n + 14
3n3 + 4n2 + 7n - 4

5n^3 + 4n^2 - 9 + (-2n^3 + 7n - 5) = 5n^3 - 2n^3 + 4n^2 + 7n - 9 - 5 = 3n^3 + 4n^2 + 7n - 14

Question

Asked 2/17/2016 12:26:29 PM

Updated 2/18/2016 4:06:27 AM

1 Answer/Comment

Rating

3

5n^3 + 4n^2 - 9 + (-2n^3 + 7n - 5)

= 5n^3 - 2n^3 + 4n^2 + 7n - 9 - 5

= 3n^3 + 4n^2 + 7n - 14

= 5n^3 - 2n^3 + 4n^2 + 7n - 9 - 5

= 3n^3 + 4n^2 + 7n - 14

Added 2/18/2016 2:01:38 AM

This answer has been confirmed as correct and helpful.

Confirmed by Andrew. [2/18/2016 4:06:30 AM]

Simplify.
[7m + 3n - 9 + 2m] + [n + 3 + m + 3n - 6]
10m + 8n - 12
10m + 7n - 12
6m + 7n - 12
6a + 7b - 15

Question

Not Answered

Updated 2/16/2016 5:50:38 PM

1 Answer/Comment

(3.125) + (-3.9) - (2.46)

Question

Not Answered

Updated 2/16/2016 10:45:05 PM

2 Answers/Comments

(3.125) + (-3.9) - (2.46)

= 3.125 - 3.9 - 2.46

= -0.775 - 2.46

= -3.235

= 3.125 - 3.9 - 2.46

= -0.775 - 2.46

= -3.235

Added 2/16/2016 5:45:55 PM

This answer has been confirmed as correct and helpful.

Confirmed by Andrew. [2/16/2016 10:46:10 PM]

27,651,955

questions answered

There are no comments.